A escrita e o womanism político negro como ascensão em A Cor Púrpura e Quarto de Despejo, diário de uma favelada - Macedo, Samantha Leite de (Universidade Federal do Tocantins, 2020)
The aim of the research is to analyze and discuss the black political thought and the womanism present in the speeches and attitudes of the female protagonists Celie in The Color Purple, by Alice Walker and Carolina Maria de Jesus in Quarto de despejo, diário de uma favelada. The work corresponds to a qualitative bibliographical approach, following the comparative bias involving the theory of confessional writing, epistolary writing and womanism. During the analysis of the literary excerpts, we perceive that the voices of these characters personified in both works reverberate an echo of struggle for visibility of gender, class, and race, besides mobilizing feminine empowerment and its movements of resistance before the ardor of europhalocentric society through the confessional writing.